2005
DOI: 10.1140/epja/i2005-10167-2
|View full text |Cite
|
Sign up to set email alerts
|

Signature of the ηNN configurations in coherent πphotoproduction on the deuteron

Abstract: The photoproduction of a neutral pion on the deuteron is considered in the energy region around the η threshold, where a bump-like structure was observed at very backward pion angles. Different dynamical aspects which may be responsible for this phenomenon are analysed within a theoretical frame which includes intermediate ηN N configurations. The results show in particular, that a three-body treatment of the ηN N interaction is of special importance.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
4
15
0
Order By: Relevance
“…At E γ < ∆(1232), one notes that the agreement between results using different elementary operators is not satisfactory. The reason for this may be due to the neglecting πN-rescattering in the intermediate state which is found to be important [7]. On the contrary, we obtained a qualitatively reasonable agreement between our results and the data from TAPS [6] at energies around the ∆-region.…”
supporting
confidence: 64%
“…At E γ < ∆(1232), one notes that the agreement between results using different elementary operators is not satisfactory. The reason for this may be due to the neglecting πN-rescattering in the intermediate state which is found to be important [7]. On the contrary, we obtained a qualitatively reasonable agreement between our results and the data from TAPS [6] at energies around the ∆-region.…”
supporting
confidence: 64%
“…The main conclusion of Ref. [10] was reproduced in another paper [11], where it was shown that in addition to the two-step process, the full dynamics in the intermediate ηNN system could be important as well.…”
Section: Introductionmentioning
confidence: 69%
“…This neglect leads to an underestimation of the π -rescattering effect, but it should not strongly affect the quality of the results (see also Ref. [11]). …”
Section: The First-order Rescatteringmentioning
confidence: 99%
See 2 more Smart Citations